Development and utilization of aerobic granules for soy sauce wastewater treatment optimization by response surface methodology - Harun, Hasnida; Anuar, Aznah Nor (Penerbit UTM Press, 2014)
This study examined some important factors for optimal aerobic granular sludge performance using soy sauce wastewater as a substrate in a lab-scale alternating anaerobic/aerobic sequencing batch reactor (SBR). The SBR was equipped with a circulation process to restrict the concentration gradient of granular biomass during the anaerobic phase. The influence of the circulation rate was investigated together with operation time on the SBR performances. Aerobic granular sludge (AGS) took 60 days to appear and the average diameter was 2.0 mm (with a maximum value of 2.5 mm). Response Surface Methodology (RSM) was used for experimental design, analysis and optimization. The results showed that the maximum COD removal (90%) and good SVI performance of 55.3 mL/g were obtained at the highest value of the operation time (60 d) and at moderate circulation rate (25.2 L/h). The maximum values of MLVSS/MLSS have been found to be 89% at the highest value of the factors (60 d and 36.0 L/h). At optimum point (33.62 L/h of circulation rate and 60 d of operation time), the amount of COD removed, MLVSS/MLSS and SVI were 86.5%, 88.8% and 58.6 mL/g, respectively.